Meta-analysis of TPACK-based Discovery Learning Model on Learning Outcomes in Elementary School Students - Sanju Aprilisia (AKADEMI TEKNIK ADI KARYA, 2024)
This study aims to determine the effect of TPACK-based discovery learning model on the learning outcomes of elementary school students. The source of data in this study comes from an analysis of 15 national journals published in 2022-2024. The process of data retrieval through the databases of google scholar, ScienceDirect and ERIC Journal. Data selection using PRISMA method in 2020. The inclusion criteria in this study are that the research must be experimental methods or quasi-experiments; research sample of elementary school students; research should be related to TPACK-based dsicovery learning models on student learning outcomes; learning materials related to mathematics and Indonesian; journals must be indexed by Science Technology Index (SINTA) and Garuda; and a sample size of > 20 students. Data analysis in this study is quantitative analysis by calculating the value of effect size assisted by JSAP application Version 0.8.5. The results concluded that the TPACK-based inquiry model had a significant influence on student learning outcomes with rES = 1,114; P < 0.001. This finding has a positive impact on PGSD teachers to implement this model in the learning process.